Produktivitas Pohon Sebagai Indikator Kesehatan Hutan di Sekitar Lokasi Wisata Pemandian Way Belerang Simpur, Kalianda, Lampung Selatan: Tree Productivity as an Indicator of Forest Health Around The Tourist Location of The Way Belerang Simpur Bathing, Kalianda, South Lampung - Larasati, Novi Yunita; Safe'i, Rahmat; Tsani, Machya Kartika (PERENNIAL, 2026)
The Way Belerang Simpur Bath in Kalianda, South Lampung, is a protected forest and village forest rich in tropical vegetation, including timber and non-timber trees. However, with the development of tourism, it puts pressure on the tree vegetation around the location on tree growth. This study aims to determine the value of tree productivity parameters (indicators) and obtain the final value around the tourist location of the simpur eagle bath, Kalianda, South Lampung as one of the indicators of forest health assessment. The method used is the creation of FHM plot clusters which results in the determination of 4 plot around the Way Belerang Simpur Bath Tourist Location. Analysis of tree productivity parameter data (indicators) using the LBD formula (Base Field Area) = 1/4 πd². The forest health assessment is obtained from the final value of forest health conditions formulated by NKH (Forest Health Value) = NT (Weighted Value) x NS (Score Value). The results showed that the values of tree productivity parameters (indicators) for each plot cluster were 85.109 m² (cluster 1), 81.455 m² (cluster 2), 128.569 m² (cluster 3), and 12.879 m² (cluster 4) each. The final value of tree productivity is 1.00 – 1.85 in the medium category. The final tree productivity score for forest health reflects that forest areas have not been managed optimally, so tree planting is needed to maintain tree growth. Thus, the value of tree productivity parameters (indicators) is 77.003. The final value of the average tree productivity is 1.60 with medium category status. The final value of tree productivity is 1.00 – 1.85 in the medium category. The final tree productivity score for forest health reflects that forest areas have not been managed optimally, so tree planting is needed to maintain tree growth. Thus, the value of tree productivity parameters (indicators) is 77.003. The final value of the average tree productivity is 1.60 with medium category status.